ROLE OF RESISTANCE EXERCISE IN CONTROLLING INSULIN-LIKE GROWTH FACTOR 1 (IGF-1) AND IT’S ASSOCIATION WITH METABOLIC DISEASE PREVENTION - Fitri Fadhilah; Abdul Hadi Hassan; Hanna Goenawan; Herry Herman; Aziiz Mardanarian Rosdianto; Ronny Lesmana (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2019)
Based on data Riset Kesehatan Dasar (Riskesdas) in 2007, the number of people who had no or low physical activity reached 48.2 %. This condition contributes to the increasing number of metabolic disease cases such as hypertension, heart disease, stroke, and diabetes mellitus. Optimizing training approaches especially the aerobic type helps to counter metabolic diseases. Unfortunately, the benefits of resistance training (RT) are less understood. RT improves muscle strength, induces muscle hypertrophy, improvement of local muscular performance, and also helps to strengthen body balance and coordination. There is an interplay between training and hormone in muscle adaptation during resistance training. The hormone plays an important role in the regeneration of muscle after resistance training. The changes in hormone level cause hypertrophy. Regeneration and muscle hypertrophy are mediated by activation, proliferation, and differentiation of satellite cells. It is regulated by mitotic and myogenic activity, namely insulin-like growth factor-1 (IGF-1), which serves as a paracrine or autocrine. A better understanding of homeostasis hormone during training in skeletal muscle and its ultimate purpose to counter metabolic disease will lead us to a better treatment approach for the patient.